Culling reduces fecal pellet deposition by introduced sambar (Rusa unicolor) in a protected water catchment - Ami Bennett; Shane Haydon; Melita Stevens; Graeme Coulson (Wildlife Society Bulletin)
ABSTRACT Introduced sambar (Rusa unicolor) occur at high density within the Upper Yarra Catchment, an important watershed for the supply of water to Melbourne, Victoria, Australia. Contamination by zoonotic pathogens in sambar fecal pellets poses a serious risk to water quality. We describe spatial and temporal patterns in distribution and density of sambar in the Upper Yarra Catchment between 2003 and 2012, and assess ground‐based culling as a technique to reduce the risk of fecal contamination of the water supply. Sambar density, as indexed by fecal pellet deposition, was inversely related to distance from the reservoir, and aggregations of up to 70 sambar occurred on open flats adjacent to the reservoir, where they foraged mostly at dusk. Culling by ground‐shooting halved fecal pellet density on these flats, primarily through short‐term deterrence rather than a significant reduction of the population. As culling continued, fecal pellet deposition declined further, reducing the likely risk to water supplies. We conclude that localized deterrence through targeted culling of sambar at this site is an effective management technique for decreasing deer fecal deposition and the risk of contamination by zoonotic pathogens of Melbourne's water supply. © 2015 The Wildlife Society.